Eight glacial cycles from an Antarctic ice core - Augustin, Laurent; Barbante, Carlo; Barnes, Piers R. F.; Marc Barnola, Jean; Bigler, Matthias; Castellano, Emiliano; Cattani, Olivier; Chappellaz, Jerome; Dahl-Jensen, Dorthe; Delmonte, Barbara; Dreyfus, Gabrielle; Durand, Gael; et al. (Nature, 2004)
The Antarctic Vostok ice core provided compelling evidence of the nature of climate, and of climate feedbacks, over the past 420,000 years. Marine records suggest that the amplitude of climate variability was smaller before that time, but such records are often poorly resolved. Moreover, it is not possible to infer the abundance of greenhouse gases in the atmosphere from marine records. Here we report the recovery of a deep ice core from Dome C, Antarctica, that provides a climate record for the past 740,000 years. For the four most recent glacial cycles, the data agree well with the record from Vostok. The earlier period, between 740,000 and 430,000 years ago, was characterized by less pronounced warmth in interglacial periods in Antarctica, but a higher proportion of each cycle was spent in the warm mode. The transition from glacial to interglacial conditions about 430,000 years ago (Termination V) resembles the transition into the present interglacial period in terms of the magnitude of change in temperatures and greenhouse gases, but there are significant differences in the patterns of change. The interglacial stage following Termination V was exceptionally long—28,000 years compared to, for example, the 12,000 years recorded so far in the present interglacial period. Given the similarities between this earlier warm period and today, our results may imply that without human intervention, a climate similar to the present one would extend well into the future.
Keywords: Antarktis; klimagasser; paleoklimatologi

Direct measurements reveal insignificant storage of anthropogenic CO2 in the Abyssal Weddell Sea - Hoppema, Mario; Roether, Wolfgang; Bellerby, Richard G. J.; de Baar, Hein J. W. (Geophysical Research Letters, 2001)
In the northern Weddell Gyre at the prime meridian, Total TCO2 changes in the Weddell Sea Bottom Water (WSBW) have been investigated. Following a suggestion by [Poisson and Chen, 1987], the TCO2 difference at potential temperatures of 0.2°C and −0.8°C was determined using data from 1996 and 1998. No significant difference was found to similar differences for the years 1973 and 1981 reported by Poisson and Chen. Thus, over a period of 25 years an at most minor amount of anthropogenic CO2 has penetrated into the WSBW at this location. This suggests that this abyssal subpolar region is relatively unimportant for the storage of anthropogenic CO2. The same core of WSBW exhibited a marked increase of chlorofluorocarbon (CFC). For the Southern Ocean, therefore, CFCs are apparently of limited value as analogues of anthropogenic CO2, in contrast to some other ocean provinces.
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; drivhusgasser; geofysikk; klimagasser

Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren